Dynamic Business Strategy Competing in a Fast-changing, Uncertain Context - Baker, Lewis; Candelon, François; Deimler, Michael; Fuller, Jack; Gandhok, TejPavan; Goulet, Kaelin; Grosvenor, James Yuji; Hamilton, Peter; Kimura, Ryoji; Legrand, Julien; Lesser, Rich; Lotan, Hen; et al. (Inspiring the next game (Series), 2022)
The playing field for business has changed significantly in recent decades. The pace of change is accelerating, driven by increased technological progress and shrinking business lifespans. Economic and political uncertainty has risen dramatically and is likely to remain at elevated levels. Industry boundaries are blurring, increasing the potential paths to competitive disruption. Strategy is not dead--in fact, as the gap between winners and losers within industries continues to grow, it is more important than ever. However, the playbook needs to be reinvented for today's business environment. Classical sources of competitive advantage, such as scale and differentiation, have not gone away, but they have been complemented by new dimensions of competition. This book discusses the new role of strategy in a dynamic, unpredictable context. Part 1 of this book revisits classical strategy frameworks and what changes should be made to apply them to the modern era. Part 2 discusses new strategic capabilities companies need today, such as adapting to uncertain environments and shaping new or disrupted ones. Part 3 examines the expanding boundaries of strategy, including new competitive imperatives as well as the wider range of timescales on which businesses must now operate. Drawing on the work of the BCG Henderson Institute and its fellows and ambassadors over several years, Dynamic Strategy will help business professionals as well as academics and students with an interest in strategy understand the new competitive challenges that businesses face and develop a playbook to address them.